2018
DOI: 10.1016/j.immuni.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17-Producing γδ T Cells Originate from SOX13+ Progenitors that Are Independent of γδTCR Signaling

Abstract: Summary Lineage-committed αβ and γδ T cells are thought to originate from common intrathymic multipotent progenitors following instructive T cell receptor (TCR) signals. A subset of lymph node and mucosal Vγ2+ γδ T cells is progγδTCR in development of these cells remains controversial. Here we generated reporter mice for the rammed intrathymically to produce IL-17 (Tγδ17 cells), however the role of the Tγδ17 lineage-defining transcription factor SOX13 and identified fetal-origin, intrathymic Sox13+ progenitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
107
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 64 publications
6
107
0
Order By: Relevance
“… T cell development is dependent on a characteristic subset of transcription factors including SOX4, SOX13, Blk, c-maf, HEB, and PLZF, among others (27,28,45,(52)(53)(54). Recently, it was reported that at least some T17 programming results from a SOX13-dominated transcriptional hard-wiring of early thymocyte precursors (29). These SOX13 progenitors appear to give rise to IL-17-producing V4, but not V6 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… T cell development is dependent on a characteristic subset of transcription factors including SOX4, SOX13, Blk, c-maf, HEB, and PLZF, among others (27,28,45,(52)(53)(54). Recently, it was reported that at least some T17 programming results from a SOX13-dominated transcriptional hard-wiring of early thymocyte precursors (29). These SOX13 progenitors appear to give rise to IL-17-producing V4, but not V6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…hardwired transcriptional programs (27)(28)(29). Exactly how these seemingly independent mechanisms converge to regulate the developmental programming of innate-like  T cell subsets remains an open question.…”
mentioning
confidence: 99%
“…As the origin of progenitors during development may be linked to the generation of distinct populations within the immune system, we revisited the controversial origin of the first wave of TSP. By analogy with the documented YS origin of tissue resident macrophages (Gomez Perdiguero et al, 2015b;Perdiguero and Geissmann, 2016), it was proposed that also early developing innate-like T cells and therefore the first TSP were HSC independent (Böiers et al, 2013;Gentek et al, 2018a;Kobayashi et al, 2014;Luis et al, 2016;Spidale et al, 2018;Yoshimoto et al, 2011Yoshimoto et al, , 2012.…”
Section: Disscusionmentioning
confidence: 98%
“…They expressed lymphoid associated genes (Il7r, Rag2, Rag1) and were proposed as the origin of the first wave of TSP (Luis et al, 2016). Independent reports have also converged to support the notion that Vg5 + and another gd T cell subset, Vg6 + IL-17 producing might originate from YS progenitors, independent of HSCs (Gentek et al, 2018a;Spidale et al, 2018). In contrast to the above studies, Vg5 + and B1a B cells were shown to be preferentially derived from a particular HSC-like subset, transiently found in the FL but not in the adult BM, marked by an history of Flk2 expression (Beaudin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although T cell receptor (TCR) signaling is necessary for γδT17 cell development (Wencker et al, 2014), experimental evidence based on hypomorphic CD3 mice and anti-CD3/TCR antibody administration suggested that only weak TCR signals are required (Munoz-Ruiz et al, 2016; Sumaria et al, 2017). In addition, a recent study showed that TCR signaling is not important for lineage specification but for transition into the early immature stage (Spidale et al, 2018). γδT17 cell generation is restricted to the embryonic and neonatal thymus (Haas et al, 2012) with the bone marrow displaying low capacity to produce these cells (Cai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%